When implementation goes wrong: Lessons from crop insurance in India - Nirmal, Rajalakshmi; Babu, Suresh Chandra (International Food Policy Research Institute, 2021)
Based on experiments to bring about comprehensive crop insurance coverage over the last 50 years, the Indian government introduced a new crop insurance program, called Pradhan Mantri Fasal Bima Yojana (PMFBY), in April 2016. Coming after two successive years of drought, the scheme aimed at reducing the burden of smallholders who borrow at high rates of interest but remain at the mercy of the “weather god” to reap optimal returns. Although this new program filled many gaps in the previous crop insurance interventions, it still could not attract smallholder and marginal farmers to fully subscribe to it. It also faced its own set of challenges. It earned farmers’ wrath because of lack of transparency in crop loss assessments and delayed settlement of claims. The government of India had to make the program voluntary under pressure from farmers’ associations, although it was designed as mandatory for famers seeking institutional credit. This paper’s focus is identifying the reasons for failure of PMFBY in most of the states despite its improved features, and comparing these states with a state where it has been relatively successful. It does this through evidence collected from a field study in Marathwada—a drought-prone region in western India, with the nation’s highest rate of farmer suicides. It takes learnings from stakeholder interviews in Marathwada to design implementation strategies for PMFBY’s success and win back the confidence of farmers. The state of Karnataka, in contrast to Marathwada, is an outlier among states in India, with a record of successful implementation of the PMFBY program. This paper studies PMFBY program implementation in Karnataka through a positive deviance case study approach. Though Karnataka hasn’t yet seen full success in terms of penetration achieved in crop insurance, its model can help develop best practices for implementation of PMFBY. The paper argues that getting buy-in from all stakeholders, adopting remote sensing technologies, strengthening infrastructure and institutional capacity, conducting outcome evaluation, and putting in place a monitoring system could be effective mechanisms to mainstream the program among smallholder farmers.